Contemporary Thought on Nineteenth Century Socialism - Morgan, Kevin, 1961- (Milton)
1 online resource (495 p.)
Keywords: For historians of the international labour movement, the decades before 1914 were the golden age of Marxist thought. In this flowering of socialist thinking, Britain seemingly had no part, and the question has been asked instead: Why was there was no Marxism in Britain?' The selections in this volume confirm that Marxist ideas in Britain were not always pitched at the highest theoretical level. There are also examples of the reductionism to which leading exponents were sometimes prone. Nevertheless, there is also a richness and outspokenness across wide and varied themes that belies the caricature of arid economic determinism. Marxists believed they carried on the tradition of home-grown movements of struggle such as Chartism. They also identified with the new spirit of internationism whose ideas and personalities filled the pages of their periodicals. Behind such well-known names as William Morris, James Connolly and Tom Mann, a wider movement of contrarians remains to be discovered.